The moments we have not chosen. Issue 3 (2nd September 2022) - Kull, Anne
Abstract: Since the Russian invasion of Ukraine and its justification by the head of the Russian Orthodox Church we have to re‐think the possibilities of our own God‐talk as well. Can we confess our unity of faith with this church, and continue to speak of peace and love? The great Russian chauvinism in its latest expression – the Russkii world – is spreading its madness. We cannot not lament the situation, we cannot turn a new page before Ukrainians and other victims of violent conflicts can do it as well.